Karakteristik Ibu Hamil Trimester III yang Mengalami Kecemasan dalam Menghadapi Persalinan pada Masa Pandemi Covid-19 di Klinik Kesehatan dan Rumah Bersalin Dewi Laksmi Nabire Papua - Ni Ketut Santhiyogi Visnu Wardani; Putu Asih Primatanti; Ni Wayan Armerinayanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Covid-19 is an acute respiratory diseasse which was spread to all countries, one of which is Indonesia. One of the impact of this pandemic is causing many restrictions on almost all services, including health services. The maternal mortality rates (MMR) in Papua reached 200 per 100,000 live births. Anxiety is a problem that if not treated immediately can cause problems for the mother and baby, including the occurrence of resistance in the uterine arteries which causes stunted fetal growth. The purposes of this study is to determine characteristics of third trimester pregnant women who experience anxiety in dealing with childbirth during the COVID-19 pandemic at the Dewi Laksmi Nabire Maternity Health Clinic and Maternity Hospital, Papua. This research uses descriptive research method with cross sectional study design with non probability sampling technique purposive sampling method. The sample consisted of 195 third trimester pregnant women who had met the inclusion and exclusion criteria. The data collection instrument used a questionnaire in the form of a google form. Data analysis was performed univariately. The result showed majority of third trimester pregnant women experienced mild-severe anxiety in the age range of 20-35 years (29.3%), had sufficient knowledge (31.1%), received support from their husbands (11.9%), not working (54.3%), primigravida (43.2%), high education level (21.2%), and getting the COVID-19 issue (28.7%). For all pregnant women, it is hoped that this research can be used as informative material that can increase understanding regarding the description level of anxiety on pregnant women that will be giving birth during COVID-19.